USE OF DYES IN KALIDAS'S PAINTINGS: कालिदास के चित्रों में रंगों का प्रयोग - Tomar, Nita (International Journal of Research -GRANTHAALAYAH, 2014)
In the field of poetry and drama, an equally extraordinary genius rich creator like Mahakavi Kalidas, will be rare in the history of world literature, who has made beautiful and accurate use of different colors as per the context in his works. Mahakavi Kalidasa's fascination for colors must have been in his psyche from the very beginning of his life, as special references to colors are found in his first work 'Ritamsakhya'. He has presented such a scheme of different colors in his creations from place to place, which easily captivates the mind. Mahakavi Kalidas has the amazing poetic power to make his similes meaningful and unique through color. काव्य एवं नाटक के क्षेत्र में एक समान असाधारण प्रतिभा के धनी महाकवि कालिदास जैसे समर्थ रचनाकार विश्व साहित्य के इतिहास में भी बिरले ही होंगे जिन्होंने अपनी कृतियों में प्रसंगानुसार यथास्थान विभिन्न रंगो का सुन्दर और सटीक प्रयोग किया है। महाकवि कालिदास के मानस में रंगों के लिए आकर्षण उनके जीवन के आरम्भ से ही रहा होगा क्योंकि उनकी प्रथम रचना ‘ऋतुसंहार’ में भी रंगों के विशेष संदर्भ मिलते हैं। उन्होंने अपनी कृतियों में स्थान-स्थान पर विभिन्न रंगों की ऐसी योजना प्रस्तुत की है, जो सहज ही मन मोह लेती है। रंगों के माध्यम से अपनी उपमाओं को सार्थक और विलक्षण बनाने की अदभुत काव्यात्मक शक्ति महाकवि कालिदास के पास है।